Exploration of cytochrome P450 inhibition mediated drug-drug interaction potential of kratom alkaloids. (1st February 2020) - Kamble, Shyam H.; Sharma, Abhisheak; King, Tamara I.; Berthold, Erin C.; León, Francisco; Meyer, P. Katharina L.; Kanumuri, Siva Rama Raju; McMahon, Lance R.; McCurdy, Christopher R.; Avery, Bonnie A.
Graphical abstract: Highlights: Mitragynine and corynantheidine are potent inhibitors of human CYP2D6. Moderate inhibitory effects of other kratom alkaloids on rest of the CYP450 enzymes. Mitragynine and corynantheidine showed competitive inhibition of CYP2D6. Mitragynine may lead to clinically significant adverse drug interactions with CYP2D6 substrates. Abstract: In vitro cytochrome P450 inhibition of major kratom alkaloids: mitragynine (MTG), speciogynine (SPG), speciocilliatine (SPC), corynantheidine (COR), 7-hydroxymitragynine (7HMG) and paynantheine (PAY) was evaluated using human liver microsomes (HLMs) to understand their drug-drug interaction potential. CYP450 isoform-specific substrates of CYP1A2, 2C8, 2C9, 2C19, 2D6, and 3A4/5 were incubated in HLMs with or without alkaloids. Preliminary CYP450 inhibition (IC50 ) data were generated for each of these isoforms. In addition, the type of inhibition and estimation of the inhibition constants (Ki ) of MTG and COR were determined. Among the tested alkaloids, MTG and COR were potent inhibitors of CYP2D6 (IC50, 2.2 and 4.2 μM, respectively). Both MTG and COR exhibited competitive inhibition of CYP2D6 activity and the Ki were found to be 1.1 and 2.8 μM, respectively. SPG and PAY showed moderate inhibition of CYP2D6 activity. Additionally, moderate inhibitory effects by SPC, MTG, and SPG were observed on CYP2C19 activity. Interestingly, inhibition of only midazolam hydroxylase CYP3A4/5 activity by COR, PAY, and MTG was observed while no inhibitory effect was observed when testosterone was used as a probe substrate. In conclusion, MTG and COR may lead to clinically significant adverse drug interactions upon coadministration of drugs that are substantially metabolized by CYP2D6.